Analisis Kualitas Layanan SIAKAD Universitas Dinamika Bangsa Jambi Menggunakan Metode Webqual 4.0: Analisis Kualitas Layanan SIAKAD Universitas Dinamika Bangsa Jambi Menggunakan Metode Webqual 4.0 - Dewi, Rosita; Dodo Zaenal Abidin; Effiyaldi (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2025)
This study aims to analyze the service quality of the SIAKAD website at Universitas Dinamika Bangsa Jambi using the WebQual 4.0 method. The issues raised include the impact of access speed, the SIAKAD system on user expectations, the completeness and accuracy of data, and an overall analysis of the SIAKAD service quality. The study uses three main variables: Information Quality, Interaction Quality, and Usability Quality, with 311 respondents categorized by gender, age, and academic program cohort. The results show that Information Quality and Interaction Quality have a significant impact on user satisfaction, while Usability Quality does not have a significant effect. An R-Square value of 85% indicates that the service quality of SIAKAD at Universitas Dinamika Bangsa Jambi is good and positively influences user satisfaction. This study concludes that users are satisfied with the quality of the SIAKAD website services, except in terms of Usability.